Pengaruh Belanja Bantuan Sosial dan Belanja Subsidi terhadap Kemiskinan di Provinsi Sumatera Utara - Nurul Dieniah Alfath; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Abstract. This research aims to analyze the influence of social assistance spending and subsidy spending on poverty in North Sumatra Province. The independent variables in this research include social assistance spending and subsidy spending, while the dependent variable is poverty. The data used comes from the North Sumatra Central Statistics Agency for the 2009-2023 period, which includes data on social assistance spending, subsidy spending and the depth of poverty. The data analysis method used is multiple linear regression. The results of this research show that social assistance spending has a positive but not significant influence on poverty, while subsidy spending has a positive and significant influence on poverty. Government spending policies in the form of subsidies and social assistance still require evaluation to increase their effectiveness in reducing poverty.